Influence of Concept Maps in Guided Inquiry Learning Reasoning Ability Judging from Grade XI - Agung Wahyudi (Jurnal Pendidikan Sains, 2013)
Pengaruh Penggunaan Peta Konsep dalam Pembelajaran Inkuiri Terbimbing Ditinjau dari Kemampuan Bernalar Siswa Kelas XI Abstract: The purpose of the research is as follows. (1) Knowing the differences in learning outcomes of students studying physics using guided inquiry learning through concept maps (PITPK) with the learning outcomes of students studying physics using guided inquiry learning (PIT). (2) Testing the interaction between PITPK the reasoning ability of learning to the learning outcomes of physics. (3) Determine the effectiveness of the learning outcomes of physics students with high reasoning ability to learn to use physics PITPK the learning outcomes of students who have high reasoning ability is learning to use the PIT. (4) Determine the effectiveness of the learning outcomes of physics students with low reasoning ability to learn to use the results to study physics students with low reasoning ability is learning to use the PIT. The research design used is a 2 x 2 factorial with sampling using simple random sampling. The research instrument is the treatment instrument, namely: observation sheets keterlaksanaan lesson plans, syllabi and treatment instruments, namely: a matter of testing the ability of reasoning and cognitive learning about the test results. Before the data dinalisis done first prerequisite test data analysis is to test Liliefors normality test and homogeneity test. Data were analyzed using ANOVA and Tukey test two paths. Results of the study are: (1) the results of studying physics students using PITPK higher than the results of student learning using the PIT, (2) there is an interaction between PITPK the reasoning ability of the physics students' learning outcomes, (3) the results of studying physics students with high reasoning ability to use PITPK higher than physics student learning outcomes using the PIT, and (4) physics student learning outcomes using low reasoning ability PITPK higher than physics student learning outcomes using the PIT. Key Words: guided inquiry learning, concept maps, learning outcomes Abstrak: Tujuan penelitian adalah sebagai berikut. (1) Mengetahui perbedaan hasil belajar fisika siswa yang belajar menggunakan pembelajaran inkuiri terbimbing melalui peta konsep (PITPK) dengan hasil belajar fisika siswa yang belajar menggunakan pembelajaran inkuiri terbimbing (PIT). (2) Menguji interaksi antara PITPK dengan kemampuan bernalar belajar terhadap hasil belajar fisika. (3) Mengeta-hui efektivitas hasil belajar fisika siswa yang mempunyai kemampuan bernalar tinggi yang belajar menggunakan PITPK dengan hasil belajar fisika siswa yang mempunyai kemampuan bernalar tinggi yang belajar menggunakan PIT. (4) Mengetahui efektivitas hasil belajar fisika siswa yang mempunyai kemampuan bernalar rendah yang belajar menggunakan dengan hasil belajar fisika siswa yang mempu-nyai kemampuan bernalar rendah yang belajar menggunakan PIT. Rancangan penelitian yang diguna-kan adalah faktorial 2 x 2 dengan pengambilan sampel menggunakan teknik simple random sampling. Instrumen penelitian berupa instrumen perlakuan yaitu: lembar observasi keterlaksanaan RPP, silabus dan instrumen perlakuan yaitu: soal tes kemampuan bernalar dan soal tes hasil belajar kognitif. Sebe-lum data dinalisis dilakukan terlebih dulu uji prasyarat analisis data yaitu uji normalitas dengan uji li-liefors dan uji homogenitas. Teknik analisis data menggunakan uji ANAVA dua jalur dan uji Tukey. Hasil penelitian adalah: (1) hasil belajar fisika siswa menggunakan PITPK lebih tinggi daripada hasil belajar siswa menggunakan PIT, (2) terdapat interaksi antara PITPK dengan kemampuan bernalar terhadap hasil belajar fisika siswa, (3) hasil belajar fisika siswa dengan kemampuan bernalar tinggi menggunakan PITPK lebih tinggi daripada hasil belajar fisika siswa menggunakan PIT, dan (4) hasil belajar fisika siswa berkemampuan nalar rendah menggunakan PITPK lebih tinggi daripada hasil belajar fisika siswa menggunakan PIT.Kata kunci: pembelajaran inkuiri terbimbing, peta konsep, hasil belajar